2019
DOI: 10.21009/jobbe.003.2.03
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Climate on Work Motivation and Its Impact on Organizational Citizenship Behavior (OCB) of Employees of Education Department in DKI Jakarta

Abstract: The objectives of this research was to study the effect of organizational climate on work motivation and its impact on organizational citizenship behavior (OCB) of Education Department employees in Province of DKI Jakarta. Quantitative approach used in this research with survey method. The samples of this research were 120 people selected randomly. The data were obtained by distributing questionnaire and analyzed by using path analysis. The first results of the research can be concluded that organizational cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…Employees with high work motivation have a better impact on Organizational Citizenship Behavior (OCB) because they show an attitude of working more than other employees as a form of their perspective on responsibility. Margahana et al, (2018); Sinaga et al, (2019); Muchtadin & Chaerudin (2020) His study also concluded that work motivation has a positive and significant effect on Organizational Citizenship Behavior (OCB).…”
Section: The Effect Of Work Motivation On Organizational Citizenship ...mentioning
confidence: 93%
“…Employees with high work motivation have a better impact on Organizational Citizenship Behavior (OCB) because they show an attitude of working more than other employees as a form of their perspective on responsibility. Margahana et al, (2018); Sinaga et al, (2019); Muchtadin & Chaerudin (2020) His study also concluded that work motivation has a positive and significant effect on Organizational Citizenship Behavior (OCB).…”
Section: The Effect Of Work Motivation On Organizational Citizenship ...mentioning
confidence: 93%
“…Both leadership and organizational climate have the ability to influence employee motivation, affecting their performance (Sinaga et al, 2019).…”
Section: Organizational Climatementioning
confidence: 99%
“…For Sinaga et al (2019), organizational climate is one of the most significant factors in maintaining employee motivation. But it's also important to set goals and objectives that employees believe are achievable to keep them motivated.…”
Section: Introductionmentioning
confidence: 99%
“…Motivasi dalam perannya meningkatkan organizational citizenship behavior dan kinerja dapat dibuktikan melalui beberapa kajian empiris. Penelitian yang dilakukan oleh (Suhardi, 2019), (Suhardi & Syaifullah, 2017), (Ibrahim & Aslinda, 2015), (Yuliusdharma et al, 2019), (Shaaban, 2018), (Suharnomo & Hashim, 2019), (Prabandari & Riani, 2018), (Hanafi et al, 2018), (Liu et al, 2019), (Sinaga et al, 2019), (Huei et al, 2014), (Putra & Sudibya, 2018) menyatakan bahwa motivasi memberikan pengaruh signifikan terhadap organizational citizenship behavior, berbeda dengan penelitian yang dilakukan oleh (Rita et al, 2018), (Wiwiek Harwiki, 2013) menyatakan bahwa motivasi memberikan pengaruh tidak signifikan terhadap organizational citizenship behavior. Berdasarkan studi empiris dapat disimpulkan bahwa motivasi memberikan pengaruh terhadap Organizational Citizenship Behavior.…”
Section: Motivasi Terhadap Organizational Citizenship Behaviorunclassified